Application of k-prototypes algorithm to smoking addiction at FST UINSU medan - Ritonga, Nurhalimah; Lubis, Riri Syafitri (Universitas Islam Negeri Raden Intan Lampung, 2024)
One of the addictive chemicals that can cause addiction is cigarettes. By combining smoking data among students of the Faculty of Science and Technology (FST) at UINSU Medan, this study seeks to overcome the problem of smoking. The K-Prototypes approach is one of the ones that is applied. Microsoft Excel 2010 and IBM SPSS Statistics are programs used to analyze research data. A sample questionnaire of FST students from UINSU Medan provided data. The findings showed that the K prototype had an impact on smoking factors, study programs, types of cigarettes, the number of cigarettes smoked, and the early age of smoking. There are 19 objects in Cluster 1, 21 objects in Cluster 2, and 25 objects in Cluster 3 students in each cluster. According to the cluster data of the K-Prototypes method, the smoking factor was caused by friends in cluster 1, which included early-age smokers (12.789) with 1.895 packs of salt warehouse cigarettes. In the second group of early smoking age groups (15.810), 1.381 packs of salt warehouse cigarettes were smoked, and the smoking factor was associated with the family. In the third group of early-age smokers (20.44), there were 1.96 packs of Marlboro cigarettes, and friends were a factor in smoking. Thus, the three study programs at FST UINSU Medan require a lot of attention from schools, families, and students.